Labour Demand and Exchange Rate Volatility - Udo Broll; Sabine Hansen (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2004)
The purpose of this paper is to assess under what conditions exchange rate volatility exerts a positive effect on a firm's labour demand. As the exchange rate volatility increases, so does the value of the export option provided the firm under study is flexible. Flexibility is important because it gives the firm option value. Higher volatility increases the potential gains from trade and may increase the demand for labour. This may explain part of the mixed empirical findings regarding the effects of exchange rate risk on labour demand and international trade.
Keywords: F16; F41; F31; F23; 330; Labour demand; Exchange rate risk; Risk aversion; Flexibility; Real option; International trade; Arbeitsnachfrage; Wechselkursrisiko; Theorie der Unternehmung; Export; Flexibilität; Realoption; Theorie